Effect of bias voltages on microstructure and mechanical properties of (AlCrNbSiTi)N high entropy alloy nitride coatings deposited by arc ion plating - Liu, Jie; Zhang, Xiangyu; Zeng, Xiaomei; Xiong, Zechang; Liu, Yan; Lei, Yan; Yang, Bing (Surface engineering, 2023)
(AlCrNbSiTi)N coatings were prepared by arc ion plating at a bias voltage in the range of −50 to −200 V. The as-deposited coatings were all found to have a face-centred cubic structure and exhibit columnar crystal. Si 3 N 4 is distributed in the columnar grains in the form of a network, which separates the columnar grains into fine grains. Si 3 N 4 presents a crystalline state and grows coherently with the surrounding grains to form a nc-(AlCrNbTi)N/nc-Si 3 N 4 nanocomposite structure. The coating with the finest mechanical characteristics was applied at −200 V. The hardness, elastic modulus and wear rate are 34.76, 425 GPa and 0.82 × 10 −9 mm 3 N −1 m −1 , respectively. Based on the outstanding mechanical performance of the coating, it is concluded that the (AlCrNbSiTi)N protective coating has a broad range of potential applications.